Geomechanical problems of an underground storage of spent nuclear fuel and their mathematic modelling - Antonín Hájek; Petr Byczanski; Radim Blaheta; Richard Šňupárek (Acta Montanistica Slovaca, 2007)
The paper is devoted to the use of mathematical modelling for analysis of the thermo-mechanical (T-M) processes, which are relevant for the assessment of underground repositories of the spent nuclear fuel. Wes shall discuss mathematical formulation, numerical methods and parallel alghorithms, which are capable to solve large-scale complicated and coupled 3D problems. Particularly, we show an application of the described methods and parallel computer simulations for analysis of model problems concerning the Swedish KBS3 concept of underground repository.